The Effect of Calcium Silicate on The Phosphorus Sorption Characteristics of Andisols Lembang West Java - Arief Hartono (Jurnal Ilmu Tanah dan Lingkungan, 2008)
The effect of calcium silicate CaSiOJ the phosphorus (P) sorption characteristics were studied in Andisols Lembang.The amount of 0, 2.5 and 5% CaSiOJ (calcium silicate) or 0, 7.5 and 15 g calcium silicate per pot was added to the 300 g(oven-dry weight) soil and incubated for one month. A completely randomized design in double replication was set up. After one month incubation, P sorption and P sorption kinetic experiments were conducted The results of P sorption experiment showed that P sorption data were satisfactorily described by the Langmuir equation. which was used to determine P sorption maxima, bonding energies and P sorbed at 0.2 mg P £"' (standard P requirement). The application of calcium silicate did not affect significantly P sorption maxima but decreased significantly the P bonding energies. Calcium silicate also decreased significantly the standard P requirements. As for P sorption kinetic experiment. the results showed that application of 5% calcium silicate decreased significantly the rate constant of P sorption and P sorbed maximum at given amount of added P. The results suggested that the application of calcium silicate to the Andisols made added P was more available for plant.